Ultralow-loss large-effective-area single-mode optical fiber
By optimizing the core cladding structure and doping alkali metals of G.654 fiber, the problem of optical fibers between reducing attenuation and maintaining a large effective area is solved, and lower transmission losses and more uniform alkali metal distribution are achieved.
Patent Information
- Application Number
- CN202411476248.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-07
AI Technical Summary
While reducing attenuation, existing G.654 optical fibers are difficult to maintain a large effective area, resulting in high transmission losses.
By optimizing the core cladding structure of the optical fiber, setting the first core layer and the second core layer, and doping alkali metal between the core layer and the cladding, adjusting the refractive index difference and viscosity distribution to reduce attenuation and increase the effective area .
It is achieved that while maintaining a large effective area, the attenuation of the optical fiber is further reduced, the transmission loss performance is improved, and the virtual temperature of the drawn optical fiber is reduced.
Smart Images

Figure CN119395807A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an ultra-low loss large effective area single-mode optical fiber, in particular to a G.654 optical fiber, and belongs to the technical field of optical communication and transmission. Background Art
[0002] With the development of the digital economy, the evolution of 5G technology has become inevitable. Compared with 5G, the "upgraded" 5G-A has the characteristics of higher speed, larger connection, and lower latency. It will increase the downlink rate to 10 Gigabit, the uplink capacity to 1 Gigabit, and the Internet of Things from tens of billions to hundreds of billions of connections. It also has new features such as deterministic experience, high-precision positioning, lightweight, and passive Internet of Things. AR navigation, VR education, industrial manufacturing, smart cities... The ubiquitous 5G-A new experience and massive computing power requirements have posed new challenges to the construction of optical networks. As the most basic and core resource in the optical network, the importance of optical fiber is self-evident. With the official commercialization of the 400G all-optical backbone network, the value of the new generation of trunk optical fiber G.654 optical fiber has become increasingly prominent and has begun to be deployed on a large scale. G.654 optical fiber has both low nonlinear effects and low attenuation coefficients, and can achieve large bandwidth, low latency, and long span backbone network transmission. Therefore, it is particularly important to develop G.654 optical fiber with lower attenuation and large effective area.
[0003] Compared with communication single-mode optical fiber, from conventional single-mode optical fiber to low-attenuation single-mode optical fiber, and then to ultra-low-attenuation single-mode optical fiber, the attenuation is continuously reduced, mainly by reducing the Rayleigh scattering coefficient of the optical fiber. The optical signal is transmitted forward by total reflection due to the difference in the refractive index of the optical fiber core and cladding. Generally, the refractive index difference is formed by doping the core with germanium, chlorine and a small amount of fluorine, and the cladding with fluorine. In glass, since GeO2 acts as a grid former like SiO2 to increase the polarizability and thus increase the refractive index, the core doping with Ge and chlorine and the cladding doping with F will reduce the viscosity of the optical fiber, but the contribution of F doping to reducing the viscosity is three times that of germanium doping, resulting in a large difference in the viscosity of the core and cladding. In the production process, viscosity mismatch will be formed, which will cause mismatch in thermal expansion and contraction at high and low temperatures, resulting in greater stress between the core and cladding, resulting in increased attenuation. Summary of the invention
[0004] The following are definitions and explanations of some terms involved in the present invention:
[0005] ppm: parts per million by weight.
[0006] Starting from the central axis of the optical fiber, according to the change in refractive index, the layer closest to the axis is defined as the core layer, and the outermost layer of the optical fiber is defined as the optical fiber cladding.
[0007] The relative refractive index difference Δni of each layer of the optical fiber is defined by the following equation:
[0008]
[0009] Where ni is the refractive index of the fiber core and nc is the refractive index of pure silica.
[0010] The effective area of the optical fiber is Aeff
[0011]
[0012] Among them, E is the electric field related to propagation, and R is the distance between the axis and the electric field distribution point.
[0013] The technical problem to be solved by the present invention is to provide an ultra-low loss large effective area single-mode optical fiber to address the deficiencies of the above-mentioned prior art. By optimizing the core-cladding structure of the optical fiber, the optical fiber has a larger effective area while further reducing attenuation.
[0014] The technical solution adopted by the present invention to solve the above-mentioned problem is: comprising a core layer and a cladding layer, characterized in that the core layer has two layers, the center is a first core layer, the radius R1 of the first core layer is 1 to 2.5 μm, the relative refractive index difference Δn1 is 0.04% to 0.12%, the second core layer is outside the first core layer, the radius R2 of the second core layer is 3.5 to 6.5 μm, the relative refractive index difference Δn2 is 0.08% to 0.12%, and Δ n1≤Δn2, the cladding includes an inner cladding and an outer cladding, the inner cladding is a fluorine-doped silica glass layer, the inner cladding radius R3 is 25 to 45 μm, the relative refractive index difference Δn3 is -0.32% to -0.20%, and Δn2-Δn3≥0.32, the outer cladding radius R4 is 62.5 μm, the relative refractive index difference Δn4 is -0.18% to -0.10%, and Δn4-Δn3≥0.
[0015] According to the above scheme, the first core layer is a germanium-chlorine-fluorine co-doped silica glass layer, the chlorine concentration contained in the first core layer is ≥7000ppm, and the chlorine content of the first core layer is lower than that of the second core layer, the germanium concentration contained in the first core layer is ≤3000ppm, and the second core layer is a high-chlorine-doped silica glass layer, and the chlorine concentration is ≥10000ppm.
[0016] According to the above scheme, alkali metals are doped in the middle of the first core layer, between the first core layer and the second core layer, and between the second core layer and the inner cladding layer. The concentration of alkali metals gradually decreases from the inside to the outside, and the content is 50 to 1500 ppm.
[0017] According to the above scheme, the alkali metal source compound is an alkali metal halide, and the halogen includes F, Cl, Br, I, and At. The alkali metal halide is any combination of the two, for example: NaF, NaCl, NaBr, KCl, KBr, etc., the added mass is 1 to 10g, and the alkali metal diffusion temperature is 780-900°C. The alkali metal source compound can also be other compounds, such as NaCO3, KNO3, etc.
[0018] According to the above scheme, the alkali metal source compound preferably has a purity greater than or equal to 99.9% and is preferably in powder form.
[0019] According to the above scheme, the relative refractive index difference of the inner cladding increases with the increase of radius, showing a gradual increase.
[0020] According to the above scheme, the attenuation of the optical fiber at a wavelength of 1550nm is equal to or less than 0.160dB / km; under preferred conditions, it is equal to or less than 0.155dB / km, and under more preferred conditions, it is equal to or less than 0.150dB / km; the attenuation of the optical fiber at a wavelength of 1625nm is equal to or less than 0.180dB / km; under preferred conditions, it is equal to or less than 0.175dB / km; under more preferred conditions, it is equal to or less than 0.170dB / km.
[0021] According to the above scheme, the effective area of the optical fiber at a wavelength of 1550nm is 110-150μm 2 .
[0022] According to the above solution, the cabled cutoff wavelength of the optical fiber is equal to or less than 1530 nm.
[0023] According to the above scheme, the optical fiber is bent 100 times with a radius of 30 mm, and the macrobending loss at a wavelength of 1550 nm is equal to or less than 0.05 dB, preferably equal to or less than 0.01 dB.
[0024] The technical solution of the preparation method of the above-mentioned alkali metal-doped optical fiber of the present invention is:
[0025] Making the first core layer core rod: firstly, doping and depositing fluorine, chlorine and germanium on a quartz liner tube by in-tube vapor deposition, then putting the fluorine, chlorine and germanium co-doped quartz liner tube into a heat preservation furnace, using heating diffusion, the alkali metal source compound at one end of the quartz liner tube is heated at a temperature of 750-900°C to provide a continuous supply of alkali metal source vapor, the temperature of the quartz liner tube is maintained at 1700-2300°C to diffuse and dope the alkali metal, the alkali metal diffusion time is 100-500 minutes, then the quartz liner tube doped with alkali metal is melted into a solid core rod, and the optical fiber preform core rod containing alkali metal in the middle of the first core layer is obtained, the alkali metal concentration gradually decreases from the inside to the outside, and the content is 50-1500ppm;
[0026] The core rod including two core layers is prepared by using an in-tube vapor deposition method to prepare a highly chlorine-doped quartz liner tube, assembling the above-mentioned alkali metal-doped chlorine-germanium-fluorine co-doped core rod and the highly chlorine-doped quartz liner tube together, placing the assembled core rod in a heat preservation furnace, using heating diffusion, the alkali metal source compound is heated at a temperature of 750-900° C. at one end to provide a continuous supply of alkali metal source vapor, the temperature of the assembled core rod is maintained at 1700-2300° C. to diffuse and dope the alkali metal, the alkali metal diffusion time is 100-500 minutes, and then the assembled core rod is melted to form a solid core rod, and the first and second core layers of the optical fiber preform core rod containing alkali metal elements are obtained, and the alkali metal concentration gradually decreases from the interface of the two core layers to the outside, and the content is 50-1500ppm;
[0027] The optical fiber preform is made by first preparing a fluorine-doped quartz sleeve including inner and outer thin layers, assembling the alkali metal-doped core rod and the fluorine-doped quartz sleeve together, placing the assembled sleeve in a heat preservation furnace, and utilizing heating diffusion. The alkali metal source compound is heated at 750-900° C. at one end to provide a continuous supply of alkali metal source steam. The temperature of the assembled sleeve is maintained at 1700-2300° C. to diffuse and dope the alkali metal. The diffusion time is 100-300 minutes. Then, the assembled sleeve is melted to form a solid optical fiber preform containing alkali metal elements at the interface between the core layer and the cladding. The alkali metal concentration gradually decreases from the core cladding interface to the outside, and the content is 50-1000ppm.
[0028] The optical fiber of the present invention can be prepared by performing a taper process on one end of the optical fiber preform rod and then clamping it in an optical fiber drawing furnace for drawing.
[0029] The beneficial effects of the present invention are as follows: 1. By optimizing the core-cladding structure of the optical fiber and adjusting the content distribution of germanium and chlorine in the first core layer and chlorine in the second core layer, it is not only possible to effectively adjust the viscosity matching between the profiles, reduce defects in the optical fiber, reduce the stress between the core cladding, and achieve lower ultra-low attenuation, but also to effectively control the crystallization problem in the process of large-scale alkali metal doping. 2. The alkali metal doping of the present invention is not only in the middle of the first core layer, between the first core layer and the second core layer, but also between the second core layer and the inner cladding. The alkali metal doping is more and wider, and the alkali metal concentration in the optical fiber is higher and more evenly transitioned from the core layer to the cladding, thereby reducing the viscosity and viscosity difference of the optical fiber, thereby reducing the virtual temperature of the drawn optical fiber, so that the transmission loss of the optical fiber is further reduced. 3. The setting of the double-core structure is beneficial to the incorporation of alkali metals in the core layer, making the core layer distribution of alkali metals more uniform. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagram of the refractive index profile of the core layer and the cladding layer according to an embodiment of the present invention.
[0031] Figure 2 Schematic diagram of the refractive index profile of the core layer and the cladding layer according to another embodiment of the present invention.
[0032] Figure 3 FIG. 4 is a radial distribution diagram of alkali metal element concentration in an optical fiber according to an embodiment of the present invention. DETAILED DESCRIPTION
[0033] The present invention is further described below in conjunction with embodiments and drawings.
[0034] It includes a core layer and a cladding layer. The core layer is co-doped with chlorine, germanium, fluorine and alkali metals. The adjacent inner cladding layer is a deeply doped F layer. The refractive index of the deeply doped F layer is constant. Figure 1 As shown, or it is deep inside and shallow outside, that is, the relative refractive index difference of the inner cladding increases with the increase of radius, showing a gradual increase, such as Figure 2 As shown. The outer cladding is a shallowly F-doped outer cladding. The radius of the first core layer is R1, the relative refractive index difference is Δn1, the radius of the second core layer is R2, the relative refractive index difference is Δn2, the radius of the adjacent inner cladding is R3, the relative refractive index difference is Δn3, and the radius of the outermost outer cladding is R4, with a refractive index of Δn4. The outer cladding diameter 2R4 is 125μm, and the final outer diameter of the optical fiber after the resin layer is removed is about 245μm.
[0035] Table 1 lists the refractive index profile parameters in the preferred embodiment of the present invention, and Table 2 corresponds to the transmission characteristics of the optical fiber.
[0036] Table 1. Refractive index profile parameters in the embodiments of the present invention
[0037]
[0038] Table 2. Parameters of optical fiber in the embodiment of the present invention
[0039]
[0040]
Claims
1. An ultra-low loss large effective area single-mode optical fiber, comprising a core layer and a cladding layer, characterized in that The core layer has two layers, the central one is the first core layer, the radius R1 of the first core layer is 1 to 2.5 μm, the relative refractive index difference Δn1 is 0.04% to 0.12%, the second core layer is outside the first core layer, the radius R2 of the second core layer is 3.5 to 6.5 μm, the relative refractive index difference Δn2 is 0.08% to 0.12%, and Δn1≤Δn2, the cladding includes an inner cladding and an outer cladding, the inner cladding is a fluorine-doped silica glass layer, the radius R3 of the inner cladding is 25 to 45 μm, the relative refractive index difference Δn3 is -0.32% to -0.20%, and Δn2-Δn3≥0.32, the radius R4 of the outer cladding is 62.5 μm, the relative refractive index difference Δn4 is -0.18% to -0.10%, and Δn4-Δn3≥0.
2. The ultra-low loss large effective area single-mode optical fiber according to claim 1, characterized in that The first core layer is a germanium-chlorine-fluorine co-doped silica glass layer, the chlorine concentration of the first core layer is ≥7000ppm, and the chlorine content of the first core layer is lower than that of the second core layer, the germanium concentration of the first core layer is ≤3000ppm, and the second core layer is a high-chlorine-doped silica glass layer, the chlorine concentration is ≥10000ppm.
3. The ultra-low loss large effective area single-mode optical fiber according to claim 1 or 2, characterized in that Alkali metals are doped in the middle of the first core layer, between the first core layer and the second core layer, and between the second core layer and the inner cladding layer. The concentration of the alkali metals decreases gradually from the inside to the outside, and the content is 50 to 1500 ppm.
4. The ultra-low loss large effective area single-mode optical fiber according to claim 3, characterized in that The alkali metal source compound is an alkali metal halide.
5. The ultra-low loss large effective area single-mode optical fiber according to claim 4, characterized in that The alkali metal source compound has a purity of greater than or equal to 99.9% and is preferably in powder form.
6. The ultra-low loss large effective area single-mode optical fiber according to claim 1 or 2, characterized in that The relative refractive index difference of the inner cladding increases with the increase of radius, showing a gradual increase.
7. The ultra-low loss large effective area single-mode optical fiber according to claim 1 or 2, characterized in that The attenuation of the optical fiber at a wavelength of 1550 nm is equal to or less than 0.155 dB / km; the attenuation of the optical fiber at a wavelength of 1625 nm is equal to or less than 0.175 dB / km.
8. The ultra-low loss large effective area single-mode optical fiber according to claim 1 or 2, characterized in that The effective area of the optical fiber at a wavelength of 1550 nm is 110 to 150 μm 2 .
9. The ultra-low loss large effective area single-mode optical fiber according to claim 1 or 2, characterized in that The cabled cutoff wavelength of the optical fiber is equal to or less than 1530 nm.
10. The ultra-low loss large effective area single-mode optical fiber according to claim 1 or 2, characterized in that The optical fiber is bent 100 times with a radius of 30 mm, and the macrobending loss at a wavelength of 1550 nm is equal to or less than 0.05 dB.
11. A method for preparing an ultra-low loss large effective area alkali metal doped single-mode optical fiber, characterized in that Making the first core layer core rod: firstly, doping and depositing fluorine, chlorine and germanium on a quartz liner tube by in-tube vapor deposition, then putting the fluorine, chlorine and germanium co-doped quartz liner tube into a heat preservation furnace, using heating diffusion, the alkali metal source compound at one end of the quartz liner tube is heated at a temperature of 750-900°C to provide a continuous supply of alkali metal source vapor, the temperature of the quartz liner tube is maintained at 1700-2300°C to diffuse and dope the alkali metal, the alkali metal diffusion time is 100-500 minutes, then the quartz liner tube doped with alkali metal is melted into a solid core rod, and the optical fiber preform core rod containing alkali metal in the middle of the first core layer is obtained, the alkali metal concentration gradually decreases from the inside to the outside, and the content is 50-1500ppm; The core rod including two core layers is prepared by using an in-tube vapor deposition method to prepare a highly chlorine-doped quartz liner tube, assembling the above-mentioned alkali metal-doped chlorine-germanium-fluorine co-doped core rod and the highly chlorine-doped quartz liner tube together, placing the assembled core rod in a heat preservation furnace, using heating diffusion, the alkali metal source compound is heated at a temperature of 750-900° C. at one end to provide a continuous supply of alkali metal source vapor, the temperature of the assembled core rod is maintained at 1700-2300° C. to diffuse and dope the alkali metal, the alkali metal diffusion time is 100-500 minutes, and then the assembled core rod is melted to form a solid core rod, and the first and second core layers of the optical fiber preform core rod containing alkali metal elements are obtained, and the alkali metal concentration gradually decreases from the interface of the two core layers to the outside, and the content is 50-1500ppm; Making an optical fiber preform: first prepare a fluorine-doped quartz sleeve including inner and outer thin layers, assemble the above-mentioned alkali metal-doped core rod and the fluorine-doped quartz sleeve together, put the assembled sleeve into a heat preservation furnace, and use heating diffusion. The alkali metal source compound is heated at 750-900°C at one end to provide a continuous supply of alkali metal source steam. The temperature of the assembled sleeve is maintained at 1700-2300°C to diffuse and dope the alkali metal. The diffusion time is 100-300 minutes. Then, the assembled sleeve is melted to form a solid optical fiber preform containing alkali metal elements at the interface of the core layer and the cladding. The alkali metal concentration gradually decreases from the core cladding interface to the outside, and the content is 50-1000ppm; Drawing into optical fiber: one end of the optical fiber preform is subjected to a taper process, and then clamped into an optical fiber drawing furnace for drawing, and the preform is drawn into a preset optical fiber through high-temperature melting.
Citation Information
Cited By
Ultra-low-loss non-dispersion shifted single-mode fiber
CN121028279A
Low-attenuation single-mode optical fiber preform, preparation method thereof and low-attenuation single-mode optical fiber
CN122344088A